2019
DOI: 10.3390/jcm8030319
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glucose Fluctuations with Sarcopenia in Older Adults with Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus accelerates loss of muscle mass and strength. Patients with Alzheimer’s disease (AD) also show these conditions, even in the early stages of AD. The mechanism linking glucose management with these muscle changes has not been elucidated but has implications for clarifying these associations and developing preventive strategies to maintain functional capacity. This study included 69 type 2 diabetes patients with a diagnosis of cognitive impairment (n = 32) and patients with normal cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 64 publications
2
33
1
3
Order By: Relevance
“…In epidemiological studies, glucose control, evaluated mainly by HbA1c, has not been found associated with sarcopenia in T2DM individuals. It is important to underline that although some studies have reported that HbA1c levels are not associated with impaired muscle quality [ 98 ], muscle strength [ 99 ], and physical performance [ 73 ], a relationship between glucose control and sarcopenia cannot be completely excluded; in fact, HbA1c levels do not adequately reflect all the aspects of the day-to-day blood glucose profile and, in particular, the occurrence of hypoglycaemic episodes and the daily glucose fluctuations that may potentially represent risk factors for sarcopenia [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…In epidemiological studies, glucose control, evaluated mainly by HbA1c, has not been found associated with sarcopenia in T2DM individuals. It is important to underline that although some studies have reported that HbA1c levels are not associated with impaired muscle quality [ 98 ], muscle strength [ 99 ], and physical performance [ 73 ], a relationship between glucose control and sarcopenia cannot be completely excluded; in fact, HbA1c levels do not adequately reflect all the aspects of the day-to-day blood glucose profile and, in particular, the occurrence of hypoglycaemic episodes and the daily glucose fluctuations that may potentially represent risk factors for sarcopenia [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…T2DM patients are known to be at high risk of developing sarcopenia due to metabolic abnormalities and insulin resistance [ 8 , 15 ]. Not only the HbA1c level but also glucose fluctuations were significantly associated with a low muscle mass, low grip strength, and slow walking speed [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the relationship between blood glucose control and frailty. In addition, poor glucose control is associated with sarcopenia as well as cognitive decline [68]. Hyperglycemia induces muscle atrophy and protein catabolism by blocking ubiquitin-dependent degradation of the transcription factor KLF15 involved in skeletal muscle loss [69].…”
Section: Hyperglycemia and Hypoglycemiamentioning
confidence: 99%
“…Hyperglycemia induces muscle atrophy and protein catabolism by blocking ubiquitin-dependent degradation of the transcription factor KLF15 involved in skeletal muscle loss [69]. Although the mechanism is not yet known, hypoglycemia is expected to negatively affect muscle homeostasis as fluctuations in blood glucose induce oxidative stress [68].…”
Section: Hyperglycemia and Hypoglycemiamentioning
confidence: 99%